The psychological and social effects of myocardial infarction on wives. Issue 6114 (18th March 1978) - Mayou, R; Foster, A; Williamson, B
Abstract : Eighty-two wives of men suffering a first myocardial infarction were interviewed while their husbands were in hospital, and again two months and a year after they went home. The wives had substantial and persistent psychological symptoms, and the husbands' illness had continuing effects on their work, leisure and social activities, and family life and marriage, their psychosocial disability being comparable to that of the patients. Measures of psychosocial adjustment before the illness and the quality of the marriage and of family life were good predictors of outcome for the wives. The women had a major role in the patients' readjustment during convalescence, and their attitudes and behaviour as well as the general quality of family life were important determinants of the rate and extent of the patients' recovery. The wives of patients with myocardial infarction should have more practical help and advice during the hospital period, and the whole family should be given advice and help throughout the convalescence.